2020
DOI: 10.33448/rsd-v9i7.4360
|View full text |Cite
|
Sign up to set email alerts
|

Produção de pimentão cultivado com pó de pedra e esterco em região semiárida

Abstract: The research was carried out aiming to verify the effect of rock powder and bovine manure as natural sources for fertilization and nutrition of the pepper culture (Capsicum annuum L. cv. All Big). The experiment was carried out in the seedling nursery of the Federal Institute of Education Science and Technology of Paraíba - IFPB, Campus Sousa, São Gonçalo Unit during the period from September 2014 to August 2015. The experimental design used was in randomized blocks (DBC ) with 10 treatments and 4 repetitions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
1
0
1
Order By: Relevance
“…Conceição et al (2022) studying basalt powder in beans, corn and soybeans, showed positive results in crop development and productivity. Mendes et al (2020) concluded in their work that the mixture between soil, manure and rock dust promoted an increase in the quality of peppers, influencing higher total and commercial production when used in the proportions 3-3-3 and 3-2-2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Conceição et al (2022) studying basalt powder in beans, corn and soybeans, showed positive results in crop development and productivity. Mendes et al (2020) concluded in their work that the mixture between soil, manure and rock dust promoted an increase in the quality of peppers, influencing higher total and commercial production when used in the proportions 3-3-3 and 3-2-2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A matéria fresca da parte aérea e raiz apresentaram os maiores valores médios nos substratos S-2, S-3 e S-4, com respectivos percentuais de 4%, 8 % e 12% de subproduto da extração de bentonita, indicando que até um determinado nível de concentração do subproduto leva o crescimento e desenvolvimento das plantas, após essa concentração pode interferir negativamente no crescimento. Mendes et al (2020) estudando o uso de pó de rocha e esterço para a produção pimentão no semiárida, verificou que na proporção de 1:1:1 de esterço, solo e pó de rocha teve os melhores rendimentos, indicando que valores mais elevados podem limitar o crescimento e desenvolvimento das plantas.…”
Section: Discussionunclassified